Regulatory T Cell and Forkhead Box Protein 3 as Modulators of Immune Homeostasis - Pereira, Leonn Mendes Soares; Gomes, Samara Tatielle Monteiro; Ishak, Ricardo; Vallinoto, Antonio Carlos Rosário (Frontiers in Immunology, 2017)
The transcription factor FOXP3 (forkhead box protein 3) is an essential molecular marker of regulatory T cell (Treg) development in different microenvironments. Treg are cells specialized in the suppression of inadequate immune responses and the maintenance of homeostatic tolerance. Studies have addressed and elucidated the role played by FOXP3 and Treg in countless autoimmune and infectious diseases as well as in more specific cases, such as cancer. Within this context, the present article reviews aspects of the immunoregulatory profile of FOXP3 and Treg in the management of immune homeostasis, including issues relating to pathology as well as immune tolerance.